2018
DOI: 10.1016/j.molliq.2018.04.055
|View full text |Cite
|
Sign up to set email alerts
|

A simple two dimensional model of methanol

Abstract: Methanol is the simplest alcohol and possible energy carrier because it is easier to store than hydrogen and burns cleaner than fossil fuels. It is a colorless liquid, completely miscible with water and organic solvents and is very hygroscopic. Here, simple two-dimensional models of methanol, based on Mercedes–Benz (MB) model of water, are examined by Monte Carlo simulations. Methanol particles are modeled as dimers formed by an apolar Lennard-Jones disk, mimicking the methyl group, and a sphere with two hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…The S/L ratio effect on extraction of these phytochemical compounds was mentioned before in Section 2.3.1, standing out that higher S/L ratios provides higher extractions yields. On the other hand, the effect of the solvent concentration on the yield could be explained by the polarity effect, we pointed out that these phytochemicals have a higher extractability with lower methanolic concentration, thus this little increase in methanol could help the extraction of other unidentified polar compounds, and due to its amphiphilic properties, it could also extract some other non-polar [39] molecules, leading to higher yields when applying this type of mixtures.…”
Section: Resultsmentioning
confidence: 95%
“…The S/L ratio effect on extraction of these phytochemical compounds was mentioned before in Section 2.3.1, standing out that higher S/L ratios provides higher extractions yields. On the other hand, the effect of the solvent concentration on the yield could be explained by the polarity effect, we pointed out that these phytochemicals have a higher extractability with lower methanolic concentration, thus this little increase in methanol could help the extraction of other unidentified polar compounds, and due to its amphiphilic properties, it could also extract some other non-polar [39] molecules, leading to higher yields when applying this type of mixtures.…”
Section: Resultsmentioning
confidence: 95%
“…[24][25][26]27,28] Recently, the effect of rotational and translational degrees of freedom on structural and thermodynamic properties of the system were studied by integral equation theory, thermodynamic perturbation theory and MC simulations. The 2D MB like methanol was introduced before by Hribar-Lee and Dill [32] and Primorac et al [33] and extended to other alcohols by Papez and Urbic [34]. Alcohol particles were modeled as 2D LJ disks with two arms separated by an angle of 120 (as in the MB model), and for each C atom in the alcohol molecule, another LJ disk of the same size was added into the molecule in the direction of a "missing" HB.…”
Section: Introductionmentioning
confidence: 99%
“…Alcohol particles were modeled as 2D LJ disks with two arms separated by an angle of 120 (as in the MB model), and for each C atom in the alcohol molecule, another LJ disk of the same size was added into the molecule in the direction of a "missing" HB. In the Hribar-Lee and Dill [32] model, the disks were overlapped, while in the model of Primorac et al [33] and Papez and Urbic [34] the disks were tangential. Hribar-Lee and Dill studied the alcohol-water mixtures, whereas Primorac et al compared both models of alcohols.…”
Section: Introductionmentioning
confidence: 99%
“…Further studies have shown that the Mercedes Benz (MB) model [14,15] qualitatively gives many properties of real water, including the density anomaly, the minimum in the isothermal compressibility as a function of temperature, the large heat capacity and the experimental trends for the thermodynamic properties of non-polar solvation [1,16,17]. The same method is used to study liquid-state methanol as well [18].…”
Section: Introductionmentioning
confidence: 99%